New Keynesian Exchange Rate Pass-Through - Cook, David (IMF Working Papers; Working Paper ;, 2008)
Using the theory of optimal local currency pricing, this paper constructs a structural equation to estimate the rate at which foreign producer prices pass through the local currency prices of imported goods in the U.S. This can be viewed as measuring exchange rate pass-through, in line with price stickiness in the New Keynesian Phillips curve literature. We estimate the structural equation using the generalized methods of moments for consistent estimates of exchange rate pass-through. We find that a model with a mix of local currency pricing and producer currency pricing fits the data best. The estimate of price stickiness in import prices is comparable to existing estimates of domestic price stickiness.